The diversity of termite species on natural forest and agroforestry land in Sulawesi tropical forests in Indonesia - Zulkaidhah, Zulkaidhah; Malik, Adam; Hapid, Abdul; Hamka, Hamka; Hariyanty, Hariyanty; Rahman, Nurulhuda (Annals of Silvicultural Research, 2024)
The conversion of natural forest to agroforestry causes physical changes in the forest, which affects the availability of organic matter. Therefore, this could influence the diversity of termites which act as decomposers in forest ecosystems. This study aims to determine the effect on the diversity of termite species of changes in tropical forest due to conversion. The study was carried out in the Educational Forest area of Tadulako University, Indonesia. The observations of environmental biophysical conditions include vegetation diversity, biomass, soil physical and chemical properties. Furthermore, using the transect method, the diversity of termite species was monitored. The results showed that the diversity of termite species decreased along with the conversion, because 13 species were found in natural forests, while only seven species were found in agroforestry land. This implies that changes in the biophysical environmental conditions due to forest conversion of tropical rainforests significantly reduced the number and composition of vegetation types at all growth rates, necromass and litter biomass. This decrease affects the availability of soil organic matter and carbon. Furthermore, these changes led not only to the loss of individual species but also to the emergence of previously unrecorded ones such as Microcerotermes dubius.